The study of Drosophila melanogaster blue cheese (bchs) function in the involvement of autophagy in neurodegenerative disorders - Sim, Joan Poh Ling (2015)
Neurodegenerative disorders are becoming an increasing concern in today's aging society whereby cognitive, postural and memory abilities are impaired in sporadic and familial forms of the disorders. Extensive research over the years has generated insights into the pathophysiological mechanisms of proteins implicated in the etiology of these diseases. A common pathological hallmark is the accumulation of cytotoxic protein aggregates in the brain that accompanies neuronal dysfunction and atrophy. The intracellular protein quality control system consists of three main components: chaperone-mediated folding, the ubiquitin-proteasome system, and autophagy. In this study, it is shown that autophagy function is impaired in Drosophila melanogaster neurodegenerative mutants in the gene blue cheese (bchs), and conversely that augmenting autophagy is sufficient to rescue the degeneration. We show this by rescuing neuronal atrophy through rapamycin feeding and atg7 over-expression. Rapamycin feeding also alleviates the accumulation of ubiquitinated aggregates in neuronal termini of bchs motor neurons. Autophagy inhibitors wortmannin and 3-methyladenine in contrast exacerbate neuronal death in bchs mutants. In the absence of Bchs protein, AtgS-positive and Atg8-positive autophagic vacuoles are not able to be recruited to ubiquitinated aggregates. Colocalization analysis and live imaging on primary neurons show that Bchs dissociates from Rabll and associates with AtgS during Huntingtin Q93 expression. However, there is no effect on the association of Bchs with Atg8 or Spinster, a late endolysosomal marker, in response to the induction of aggrephagy. These findings suggest that Bchs is involved in the early steps of autophagosome formation and recognition of target substrates, in a similar manner as the human homologue Autophagy Linked FYVE (ALFY) protein. Bchs is unlikely to be a motor protein adaptor mediating cargo assembly due to the absence of interaction with dynein or kinesin compared to APP-Iike interacting protein 1 (Aplipl). Therefore, this study demonstrates that Bchs functions as an adaptor bridging the autophagy machinery to aggregate-prone proteins using a neurodegenerative disease model in Drosophila melanogaster.